Pengaruh Latihan Hollow Sprint Dan Repetition Sprint Terhadap Kecepatan Lari Siswa Ekstrakulikuler Futsal SMP N 33 Semarang (Universitas Negeri Semarang, 2021)
Futsal is one of the most popular sports among the public today, including the activities most interested in Junior High School Negeri 33 Semarang students, shown by registered participants in this activity. Speed is an element of mobility that a futsal player must have because with high speed, players who dribble can break through and weaken the opponent's defense. However, when playing the game, students are slow to move and easily get tired when running after the ball or looking for a place so that the sprint speed has decreased. The purpose of this study was to increase the running speed of futsal extracurricular students. The population in this study were extracurricular Futsal students at Junior High School Negeri 33 Semarang, the population was 20 students, the sample was 20 students. The sampling technique uses simple random sampling technique, which is said to be simple because the sampling of sample members from the population is done randomly without paying attention to the strata in the population. The independent variable in this study is the exercise using the hollow sprint method and the repetition sprint method. The dependent variable in this study is the sprint speed of 40 meters. Statistical data analysis using the short t-test formula. From the results of data analysis, the t-count value in the hollow sprint group shows that the initial test has a value of 5.701 and the t-count value in the hollow sprint group shows that the initial test has a value of 8.193 while the t-table value with degrees of freedom (df ) 9 and the 5% significance level is 1,833. The t-count value is greater than the t-table value, thus there is a significant effect on the results of running speed in the hollow sprint group and the repetition sprint group. And from the results of the difference analysis in the hollow sprint group and the repetition sprint group, it is known that the t-count value is 3.644 while the t-table value with degrees of freedom (df) 9 and a significance level of 5% is 1.833. The t-count value is greater than the t-table value, thus there is a significant difference in the results of running speed in the hollow sprint group and the repetition sprint group. The results of the study can be concluded that there are differences in the results of training using the hollow sprint method and the repetition sprint method. The results of training using the repetition sprint method are better and more effective. Thus, for PJOK teachers and futsal extracurricular trainers at Junior High School Negeri 33 Semarang, in increasing running speed, it is recommended to use the repetition sprint training method because the effect is better than the hollow sprint training method.